Study of the Effect of 3D Printing Parameters on the Dielectric Constant in Piezoelectric Polylactic Acid/Barium Titanate Composites via Fused Granular Fabrication - Rodrigo Ruz; Dreidy Vasquez; Rodrigo Ortiz; Francisco Pizarro (IEEE Access)
This research aims to study the fabrication of electronic devices using pellet extrusion 3D printing with composite material. The process employed a polymer-based composite material that incorporated a substantial amount of barium titanate powder, reaching 80 wt.%. A thorough examination was conducted to understand the various factors influencing the printed components, using a design of experiments (DOE) approach. This method identifies the optimal printing parameters for a Custom Fused Granular Fabrication printer, such as layer height (0.32), barrel temperature (240°C), flow rate (500), and printing speed (2 mm/s). The dielectric constant of the polylactic acid - barium titanate composite reached 8.47 and a loss tangent of 0.099 in the X-band, making it suitable for applications involving high frequencies with a lower cost process and using a more sustainable polymer.